The Systolic and Diastolic Cardiac Function of Patients With Type 2 Diabetes Mellitus: An Evaluation of Left Ventricular Strain and Torsion Using Conventional and Speckle Tracking Echocardiography - Yang, Qing-mei; Fang, Jian-xiu; Chen, Xiao-yan; Lv, Hong; Kang, Chun-song (Frontiers in Physiology, 2022)
Objectives: This study aimed to quantify left ventricular (LV) myocardial strain and torsion in patients with type 2 diabetes mellitus (T2DM) and evaluate their systolic and diastolic function using conventional and speckle tracking echocardiography. Methods: Forty-seven patients with T2DM were divided into a group without microvascular complications (the DM A group) and a group with microvascular complications (the DM B group), while another 27 healthy participants acted as the control group. All the participants had had an echocardiography examination. All the original data were imported into EchoPAC workstation for the analysis and quantification of LV strain and torsion. Results: Compared with the control group, the LV end-diastolic volume, end-systolic volume, and ejection fraction of the DM A and DM B groups showed no significant differences, but the global longitudinal strain and the global circular strain were reduced in the DM B group. There were significant differences in the left ventricular relative wall thickness (RWT), left ventricular mass index（LVMI）, the early mitral valvular blood flow velocity peak/left ventricular sidewall mitral annulus late peak velocity, left ventricular sidewall mitral annulus early peak velocity/left ventricular sidewall mitral annulus late peak velocity, isovolumic relaxation time, peak twisting, peak untwisting velocity (PUV), untwisting rate (UntwR), time peak twisting velocity (TPTV), and time peak untwisting velocity (TPUV) between the DM A, DM B, and control groups. While the peak twisting velocity (PTV) was slower in the DM B group compared with the control group, the RWT, PTV, PUV, UntwR, TPTV, and TPUV in the DM B group were significantly different from the DM A group. Conclusion: The cardiac function of patients with T2DM in its early stages, when there are no microvascular complications, could be monitored with the analysis of two-dimensional strain and torsion.